Miracle fruit seed as a potential supplement for the treatment of learning and memory disorders in Alzheimer’s disease - Huang, Xue-Yan; Xue, Lu-Lu; Chen, Ting-Bao; Huangfu, Li-Ren; Wang, Ting-Hua; Xiong, Liu-Lin; Yu, Chang-Yin (Frontiers in Pharmacology, 2023)
Currently, the treatment of Alzheimer’s disease (AD) is still at the stage of symptomatic treatment and lack of effective drugs. The research on miracle fruit seeds (MFS) has focused on lipid-lowering and antidiabetic effects, but no therapeutic effects have been reported in AD. The purpose of this study was to provide data resource and a potential drug for treatment of AD. AD mice model was established and treated with MFS for 1 month. Morris water maze test was used to assess learning memory function in mice. Nissl staining was used to demonstrate histopathological changes. MFS was found to have therapeutic implications in AD mice model, as evidenced by improved learning memory function and an increase in surviving neurons. To explore the mechanism of MFS in treating AD, network pharmacological approaches, gene ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG) and molecular docking studies were carried out. Based on the network pharmacology strategy, 74 components from MFS corresponded to 293 targets related to the AD pathology. Among these targets, AKT1, MAPK3, ESR1, PPARG, PTGS2, EGFR, PPARA, CNR1, ABCB1 and MAPT were identified the core targets. According to the relevant number of core targets, cis-8-Octadecenoic acid, cis-10-octadecenoic acid, 2-dodecenal, and tetradecane are likely to be highly correlated with MFS for AD. Enrichment analysis indicated the common targets mainly enriched in AD and neurodegeneration-multiple disease signaling pathway. The molecular docking predictions showed that MFS stably bound to core targets, specifically AKT1, EGFR, ESR1, PPARA and PPARG. MFS may play a therapeutic role in AD by affecting the insulin signaling pathway and the wnt pathway. The findings of this study provide potential possibilities and drug candidates for the treatment of AD.